Geopolitical Risk and Extreme Spillovers Among Oil-Based Energy Commodities - Evžen Kočenda; Peter Albrecht; Daniel Pastorek (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We investigate the impact and propagation of geopolitical risk among oil-based energy commodities. First, we endogenously identify key geopolitical events affecting the connectedness among the oil-based commodities and then evaluate their transitory and persistent impacts. We identify four major shocks that resulted in persistent shifts in connectedness: the 9/11 attacks, the Crimea crisis, the political shift in Nigeria, and the Russian invasion of Ukraine. Using a quantile-based framework, we demonstrate that volatility transmissions due to geopolitical risk are not uniform but significantly depend on market conditions. Notably, heating oil and crude oil are identified as primary transmitters of risk, especially during economic turmoil. We quantify the negative economic and financial impacts of geopolitical risks through a multivariate dynamic portfolio analysis and through an impact on the profitability of ten global banks with high exposure to oil commodities. Our findings enhance the understanding of how geopolitical shocks influence connectedness and informed portfolio decisions, highlighting the need for adaptive strategies in finance.
Keywords: C32; C58; G15; Q02; Q35; 330; geopolitical risk; extreme market conditions; oil-based energy commodities; volatility connectedness; transitory and persistent effects; portfolio composition and hedging; global banks with high exposure to oil